An Approach to 18th Century American Exploration Using Automatic Correspondence Analysis - Kiektik, Mario Lucas; García Fiorini, Andres Lucas (AWARI, 2020)
The relationship between America and Europe has been characterized by asymmetry. Towards the end of the 18th century, in the face of the English boom, the Spanish crown began a series of reforms, including sponsoring scientific expeditions. Among them is the one directed by José Celestino Mutis. This work, which mainly uses text mining techniques and analysis of social networks, addresses the understanding of this exploratory project, its motives, difficulties, and consequences, through the automated study of the epistolary file of the aforementioned scientist during the period 1760- 1808. The results of the processing and interpretation were put in relation to the known antecedents, regarding the author's interests, type of relationships, and resources that he implemented to carry out his project and how this was expressed in the correspondence.